Reconciliation, Forgiveness and Violence in Africa: Biblical, pastoral and ethical perspectives - Nel, Marius J; Thesnaar, Christo H; Forster, Dion a (African Sun Media, 2020)
What might reconciliation and forgiveness mean in relation to various forms of personal, structural, and historical violence across the African continent? This volume of essays seeks to engage these complex, and contested, ethical issues from three different disciplinary perspectives – Biblical Studies, Systematic Theology and Practical Theology. Each of the authors reflects on aspects of reconciliation, forgiveness and violence from within their respective African contexts. They do so by employing the tools and resources of their respective disciplines. The end result is a rich and textured set of interdisciplinary theological insights that will help the reader to navigate these issues with a greater measure of understanding and a broader perspective than what a single approach might offer. What is particularly encouraging is that the chapters represent research from established scholars in their fields, recent PhD graduates, and current PhD students. This is the first book to be published under the auspices of the Unit for Reconciliation and Justice in the Beyers Naudé Centre for Public Theology.